Dando voz ao herdeiro - Bueno, Renata de Fátima Fortes (2018)
This research is aimed at understanding the motivations that an heir has for their own career and also understanding how family relations could influence their choices, seeking to analyze the benefits as a tool from the narrative practice: "Professional Tree of life of an Heir”, as a set to express feelings, and complementing traditionally techniques once used in the process of career’s orientation. This qualitative research was accomplished working with eighteen heirs, through semi-structured interview and a genogram. It was complemented with the acceptance documents of six of these eighteen heirs to experience the tool the tree of life. To analyze the results, we proceeded by using techniques of triangulation in order to deepen and enrich the information collected. The relationship between heir and family was understood according to a systemic view taking into account the construction of the heir's personal and professional identity through the process of differentiation as well as family loyalties. The results showed how beliefs, values and family references are fundamentally recognized in the construction of personal skills, professional choices and future projections, taken from the Heir's Professional Tree of Life. They also showed how the differentiation process with the original family and feelings of loyalty had interfered with the professional choices inside the family’s business. These results strengthen our belief that giving voice to an heir is invaluable, as the Heir's Professional Tree of Life also is to this research. (Apoio Capes)